Morphology and phylogeny of a new species, Pseudocercospora haldinae (Mycosphaerellaceae) on Haldina cordifolia from India - Yadav, Sanjay; Verma, Sanjeet Kumar; Singh, Vinay Kumar; Singh, Raghvendra; Singh, Archana; Kumar, Shambhu (Phytotaxa, 2021)
Pseudocercospora haldinae, a new anamorphic foliicolous hyphomycetous fungus discovered on living leaves of Haldina cordifolia (Rubiaceae) is taxonomically described and illustrated. This species is compared with closely related species of Pseudocercospora and other dematiaceous cercosporoid forms reported on the same host genus. The phylogeny of this species has been inferred from partial nuclear ribosomal 28S large subunit (LSU) and complete internal transcribed spacer (ITS) rDNA sequence data. On the basis of LSU, P. haldinae represents characteristic features of Pseudocercospora s. str. and did not form red crystals when cultivated on agar media.